A simple and robust digital current control technique of a PM synchronous motor using time delay control approach. - Kyeong-Hwa Kim (IEEE Transactions on power electronics)
A simple and robust digital current control technique of a permanent magnet (PM) synchronous motor using a time delay control approach is presented. Among the various current control schemes for a voltage source inverter-fed PM synchronous motor drive, the predictive control is known to give a superior performance. This control technique, however, requires the full knowledge of machine parameters and operating conditions, and gives an unsatisfactory response under the parameter mismatch between the motor and controller. To overcome such a limitation, the disturbances caused by the parameter variations are estimated by using a time delay control approach and used for the computation of the reference voltages by a simple feedforward control. Thus, the steady-state control performance can be significantly improved in an extremely simple manner, while retaining the good characteristics of the predictive control such as the good transient response and stable inverter operation. The proposed control scheme is implemented on a PM synchronous motor using the software of DSP TMS320C30 and the effectiveness is verified through the comparative simulations and experiments